Laterally attached kinetochores recruit the checkpoint protein Bub1, but satisfy the spindle checkpoint - Shimogawa, Michelle M (Landes Bioscience, 2010)
Kinetochore attachment to the ends of dynamic microtubules is a conserved feature of mitotic spindle organization that is thought to be critical for proper chromosome segregation. Although kinetochores have been described to transition from lateral to end-on attachments, the phase of lateral attachment has been difficult to study in yeast due to its transient nature. We have previously described a kinetochore mutant, DAM1-765, which exhibits lateral attachments and misregulation of microtubule length. Here we show that the misregulation of microtubule length in DAM1-765 cells occurs despite localization of microtubule associated proteins Bik1, Stu2, Cin8 and Kip3 to microtubules. DAM1-765 kinetochores recruit the spindle checkpoint protein Bub1, however Bub1 localization to DAM1-765 kinetochores is not sufficient to cause a cell cycle arrest. Interestingly, the DAM1-765 mutation rescues the temperature sensitivity of a biorientationdeficient ipl1-321 mutant, and DAM1-765 chromosome loss rates are similar to wild-type cells. the spindle checkpoint in DAM1-765 cells responds properly to unattached kinetochores created by nocodazole treatment and loss of tension caused by a cohesin mutant. progression of DAM1-765 cells through mitosis therefore suggests that satisfaction of the checkpoint depends more highly on biorientation of sister kinetochores than on achievement of a specific interaction between kinetochores and microtubule plus ends.